2007
DOI: 10.1192/bjp.bp.106.022590
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary-adrenal axis response in borderline personality disorder without post-traumatic features

Abstract: Hypothalamic-pituitary-adrenal (HPA) axis sensitivity was investigated in 32 non-medicated patients with borderline personality disorder without comorbid post-traumatic syndromes and in 18 normal individuals using a modified dexamethasone suppression test (0.25 mg). Enhanced cortisol suppression was found in the patients v. controls (P<0.05) and the percentage of participant's with non-suppression was smaller in the patient (34%) than in the control group (89%) (P<0.01). Baseline cortisol levels in the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 9 publications
0
29
1
3
Order By: Relevance
“…One mechanism underlying this 'de-exaggerated' HPAA response could be that by eliminating fasting as an acute but constant trigger for HPAA hyperactivity, an underlying long-term exhaustion of the HPAA may become apparent, which makes individuals vulnerable for psychological disorders in line with the theory of allostatic overload [11,78,79]. Interestingly, a similarly blunted HPAA response was also described for subgroups of patients with posttraumatic stress disorder and borderline personality disorder [80,81], panic disorder [82,83], binge-eating disorder [84], and for patients at the onset of a psychosis [85]. A common feature in these disorders is a generally stronger degree of anxiety and a lack of emotional coping.…”
Section: Discussionmentioning
confidence: 98%
“…One mechanism underlying this 'de-exaggerated' HPAA response could be that by eliminating fasting as an acute but constant trigger for HPAA hyperactivity, an underlying long-term exhaustion of the HPAA may become apparent, which makes individuals vulnerable for psychological disorders in line with the theory of allostatic overload [11,78,79]. Interestingly, a similarly blunted HPAA response was also described for subgroups of patients with posttraumatic stress disorder and borderline personality disorder [80,81], panic disorder [82,83], binge-eating disorder [84], and for patients at the onset of a psychosis [85]. A common feature in these disorders is a generally stronger degree of anxiety and a lack of emotional coping.…”
Section: Discussionmentioning
confidence: 98%
“…8 Although the results have been mixed, borderline PD, with or without posttraumatic stress syndrome, has been associated with dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis. 27,31,32 HPA-axis dysregulation has a negative impact on established cardiovascular-disease risk factors, 33 and it is associated with early atherosclerosis. 34 A recent study suggests that HPA-axis dysregulation is a mediating factor between depression and increased risk of cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators also used an even lower DEX dose of 0.25 mg, with the expectation that it may be a more sensitive test for hypersuppression. The authors suggested that their finding of hypersuppression in BPD subjects without PTSD could be related to an increase in lymphocyte glucocorticoid receptor density, 67 presumably a marker of previous exposure to chronic and severe stress, similar to what has been found in PTSD. Importantly, the authors noted that the findings could not be generalized to all individuals with BPD since their subjects were selected for a history of repetitive self-harm.…”
Section: The Dst In Studies Of Borderline Personality Disorder: the Smentioning
confidence: 62%
“…89 Only one study demonstrated hypersuppression in BPD subjects (without concurrent MDD or PTSD) compared to a normal healthy sample. 67 This study reported the degree of cortisol suppression significantly correlated with the clinical severity of BPD but not with scores on a childhood trauma questionnaire.…”
Section: The Dst In Studies Of Borderline Personality Disorder: the Smentioning
confidence: 68%
See 1 more Smart Citation